Oropharyngeal Squamous Cell Carcinoma: HPV as a Driver for Surgical Innovation - Valensise, Carolina; Rudd, James; Fraser, Lisa (Journal of the Nuffield Department of Surgical Sciences, 2023)
A case report and narrative article on the role of HPV in the surgical management of oropharyngeal squamous cell carcinoma.